Influence of sublethal concentrations of diazinon on the contents of lysozyme in serum and some organs of grass carp (Ctenopharyngodon idella, Cuvier & Valenciennes ) - Pourgholam, R.; Hassan, M. D.; Shariff, M. (Universiti Putra Malaysia Press, 2004)
The level of lysozyme in serum, spleen and kidney of grass carp (Ctenopharyngodon idella) ) weighing 850±155 g were determined at 1, 7, 15, 30 and 45 days post exposure to various sublethal bath concentrations of diazinon (1, 2 and 4 mg/L) for 12 hours at 202ºC. There was no significant difference in levels of lysozyme in tissues of spleen and kidney as compared to control fish after one day post exposure of toxicant. At 7 days post exposure the levels of lysozyme in both spleen and kidney of fish exposed to 2 and 4 mg/ L of toxicant were significantly higher than control fish (P<0.05). However at 15 days following exposure, the level of lysozyme activity had fallen back to levels similar to those recorded in control fish. The highest level of lysozyme was recorded at concentration of 4 mg / L of diazinon at 7 days of exposure of fish to the toxicant. The level of lysozyme in serum of grass carp was significantly (P<0.05) decreased in all concentrations of diazinon only at one day post exposure. The lowest level of lysozyme in serum was recorded at concentration of 4 mg / L after one day of exposure. The data show that the lysozyme content in serum and tissues of grass carp were variable and the fluctuations were defined by duration of sampling and concentration of toxicant.